About antifouling solutions to protect ship’s hull - Aurel-Dan Maimon (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2024)
Antifouling solutions are essential for protecting ship hulls from marine organisms like algae, barnacles, and molluscs, which can slow down the ship and increase fuel consumption. They are crucial for maintaining a ship's efficiency and longevity by protecting the hull from marine growth, which can slow the vessel and increase fuel consumption. Modern antifouling methods, such as specialized paints, copper-based coatings, self-polishing surfaces, silicone coatings, ultrasonic systems, and electrolytic solutions, offer effective ways to combat biofouling. These solutions not only improve operational performance but also contribute to environmental sustainability by reducing the need for frequent cleaning and minimizing the release of harmful biocides into the water. The ongoing development of innovative antifouling technologies will continue to enhance the protection and efficiency of maritime vessels.